(untitled) (Al-Qamar, 2020)
This paper studies and critically analysis Tamannā Imādī’s (1888-1972) views on the compilation of the Quran in the early Islamic period. Muslims generally believe that complete Quran had been written in the Prophetic period but it was compiled during the caliphate of the first caliph Abū Bakr. Contrary to tis general belief, Imādī claimed that it was written and compiled in prophetic period. He argues for his views by those verses of the Quran in which it is called “al-Kitāb” (the book or scripture) and by some narrations. The study supporting the traditional stance and refuting Imādī’s views concludes that Quran was not compiled in Prophetic era rater it was compiled later.